Colorimetric tests for diagnosis of filarial infection and vector surveillance using non-instrumented nucleic acid loop-mediated isothermal amplification (NINA-LAMP) - Poole, Catherine B. (PLoS One, 2017)
Accurate detection of filarial parasites in humans is essential for the implementation and evaluation of mass drug administration programs to control onchocerciasis and lymphatic filariasis. Determining the infection levels in vector populations is also important for assessing transmission, deciding when drug treatments may be terminated and for monitoring recrudescence. Immunological methods to detect infection in humans are available, however, cross-reactivity issues have been reported. Nucleic acid-based molecular assays offer high levels of specificity and sensitivity, and can be used to detect infection in both humans and vectors. In this study we developed loop-mediated isothermal amplification (LAMP) tests to detect three different filarial DNAs in human and insect samples using pH sensitive dyes for enhanced visual detection of amplification. Furthermore, reactions were performed in a portable, non-instrumented nucleic acid amplification (NINA) device that provides a stable heat source for LAMP. The efficacy of several strand displacing DNA polymerases were evaluated in combination with neutral red or phenol red dyes. Colorimetric NINA-LAMP assays targeting Brugia Hha I repeat, Onchocerca volvulus GST1a and Wuchereria bancrofti LDR each exhibit species-specificity and are also highly sensitive, detecting DNA equivalent to 1/10-1/5000(th) of one microfilaria. Reaction times varied depending on whether a single copy gene (70 minutes, O. volvulus) or repetitive DNA (40 min, B. malayi and W. bancrofti) was employed as a biomarker. The NINA heater can be used to detect multiple infections simultaneously. The accuracy, simplicity and versatility of the technology suggests that colorimetric NINA-LAMP assays are ideally suited for monitoring the success of filariasis control programs.